6y=-3x(2)-4

Simple and best practice solution for 6y=-3x(2)-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6y=-3x(2)-4 equation:


Simplifying
6y = -3x(2) + -4

Reorder the terms for easier multiplication:
6y = -3 * 2x + -4

Multiply -3 * 2
6y = -6x + -4

Reorder the terms:
6y = -4 + -6x

Solving
6y = -4 + -6x

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Divide each side by '6'.
y = -0.6666666667 + -1x

Simplifying
y = -0.6666666667 + -1x

See similar equations:

| (x+2)*3=(x-10)*7 | | 6(7g-16)=4(6g+12) | | 52=p | | -8(-6x+6)=-4x+4 | | -5v-38=-3(5v-4) | | 25200(1/10) | | 5x+83=29 | | -48-6x=(-3x)+12 | | 8.3+6x=8.6 | | 6=-3(2)-4 | | 31=w/3+31 | | z2=25/49 | | -9(-4)+7=25+2(5--7) | | 3.6x=1.6x+24 | | 16.65-8.5c+17.66=11.87-9.7c | | u=2(8n+30)+5(n+1) | | P=2(100)+2(200) | | 3x^2+6x+k=0 | | 50=-2+13x | | 25200*(1/5) | | 13=5+3b-1 | | y2=16/64 | | -5.3b-15.16=-5.1b-11.72 | | 25200*(1/4) | | 7T+18-7=41 | | 2.5t-t=3+105t | | 9-1/2=5+4n | | 35-x=2/5x | | 3p-45=-20 | | 7x+8x-40=80-5x | | x+7x=56 | | -5(7y+9)= |

Equations solver categories